Teori Kekuasaan Michel Foucault: Tantangan bagi Sosiologi Politik - Mudhoffir, Abdil Mughis (UI Scholars Hub, 2013)
Power is often discussed in political discourse or in political sociology. In this context, power is understood as the attribution, capacity, or capital to achieve certain goals of the owners. Foucault does not reject this argument, but this perspective would not be able to expose the invisible subjugation. The more critical view of power appears in cultural studies. Gramsci’s concept of hegemony is often used to dismantle the cultural establishment in the process of domination that was veiled. The more sophisticated findings, power has surpassed even the hegemonic ways, which is factually or coined by Foucault as governmentality. This paper discusses the core concepts in the Foucault’s theory of power. In addition, I also presented a debate between relation of dominance and relation of power that often overlap understood in political studies or political sociology